Asset poverty in the United States, 1984 - 1999: evidence from the panel study of income dynamics - Asena Caner; Edward N. Wolff (Levy Economics Institute of Bard College, 2002)
Using PSID data for the years 1984 to 1999, we estimate the level and severity of asset poverty. Our results indicate that the share of asset-poor households remained almost the same and the severity of poverty increased during this period, despite the growth in the economy and the financial markets. The race, age, education, and marital status of the household head, and homeownership, are important determinants of asset poverty. There seems to be a downward trend in the contribution to asset poverty of being a college graduate, a married elderly or a black head of household, a single mother, or a married person with children. The contributions of not having a college degree, being a 35 to 49 year-old household head, being a childless nonelderly couple, or being an unmarried elderly person seem to have increased. The contribution to net worth poverty of being a homeowner also went up. Descriptive statistics suggest that changes in the value of assets are more effective in transitions into and out of asset poverty than are changes in debt. Some lifetime events, such as changes in marital, homeownership, or business ownership status, are also correlated with the transitions.
Keywords: 330